Integration of Non-Targeted Metabolomics and Targeted Quantitative Analysis to Elucidate the Synergistic Antidepressant Effect of Bupleurum Chinense DC-Paeonia Lactiflora Pall Herb Pair by Regulating Purine Metabolism - Chen, Jiajun; Li, Tian; Qin, Xuemei; Du, Guanhua; Zhou, Yuzhi (Frontiers in Pharmacology, 2022)
Bupleurum chinense DC (Chaihu)-Paeonia lactiflora Pall (Baishao) is among the most commonly herb pairs in many classic prescriptions for antidepressants. Our previous study has shown that Chaihu-Baishao herb pair (CBHP) had better antidepressant effect than Chaihu or Baishao. Nevertheless, the synergistic antidepressant mechanism of this herb pair was not clearly understood. Herein, the aim of this study was to investigate the compatibility mechanism of CBHP for treating depression through a novel strategy of non-targeted metabolomics combined with targeted quantitative analysis and molecular biology techniques. Firstly, the compatibility effects of CBHP were assessed by the chronic unpredictable mild stress (CUMS) rat model. Next, cortex metabolomics based on ultra-high-performance liquid chromatograpy combined with quadrupole orbitrap mass spectrometry (UPLC-Q-Orbitrap/MS) was used to discover the metabolic pathway that was synergistically regulated by CBHP. Based on the results of metabolomics analysis, metabolites were quantitatively validated by UPLC-MS/MS combined with MRM mode in crucial metabolic pathway. Additionally, the signaling pathway associated with this metabolic pathway was detected by molecular biology techniques, to further identify the biological meaning of crucial metabolite on the synergistic antidepressant effect of CBHP. The antidepressant effect of CBHP was significantly better than Chaihu or Baishao single administrated in the behavioral test. According to cortex metabolomics, a total of 22 differential metabolites were screened out, and purine metabolism was selected as the crucial metabolic pathway by the enrichment analysis of differential metabolites. Subsequently, the purine metabolism was confirmed as disorders in the CUMS group by targeted quantitative analysis, CBHP regulated more purine metabolites (6) than individual administration (2&2). The results showed that purine metabolism was modulated by CBHP through synergistically decreasing xanthine levels and inhibiting the conversion of xanthine dehydrogenase (XDH) to xanthine oxidase (XOD). Finally, the synergistic regulation effect of CBHP on xanthine synthesis was found to be related to the inhibition of malondialdehyde (MDA) production, Nod-like receptor protein 3 (NLRP3) infammasome expression and interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α secretion. The present study demonstrated that the regulation of purine metabolism, the suppression of oxidative stress and inflammatory responses in cortex were involved in the synergistic antidepressant effect of CBHP.